Sonographic detection of an infected maternal urachal cyst during pregnancy. Issue 5 (5th October 2017) - Sargent, James; Sohaey, Roya; Trivedi, Neha
Abstract: Infection of a maternal urachal cyst during pregnancy is rare; Sonography is an important diagnostic tool that can help minimize maternal and fetal complications. We describe the case of a 35‐year‐old multiparous woman presenting in the third trimester with 2 weeks of fever, abdominal pain, and urinary symptoms. Imaging showed a 5‐cm complex anterior midline mass, found intraoperatively to be eroding into the uterus. Sonographic imaging aided in the diagnosis and management of the urachal cyst, and antepartum sonographic measurements of the lower uterine segment helped to counsel regarding a trial of labor. Following treatment, the patient stabilized and had an uncomplicated vaginal delivery.